THU0244 Additive value of scleroderma health assessment questionnaire (SHAQ) scores over haq disability index values for measuring disability and quality of life in patients with systemic sclerosis. (23rd January 2014) - Becker, C.; Huscher, D.; Becker, M.O.; Hunzelmann, N.; Riemekasten, G.
Abstract : Background: Systemic sclerosis (SSc) is a severe multisystem disorder affecting skin and a wide variety of internal organs. Clinical symptoms such as digital ulcers or organ manifestations are associated with significant morbidity and mortality as well as progressing functional disability and reduced quality of life.There is an urgent need to identify sensitive and validated measures of disability and quality of life as well as to recognise factors affecting quality of life in patients with systemic sclerosis. Objectives: Recent data raised concerns about the the additive value of aggregate SHAQ scores, and therefore, about the assessment of disease-specific symptoms, over HAQ-DI values in clincial studies. Methods: 1, 085 questionnaires from 435 consecutive SSc patients were analysed for the validation of the German Scleroderma Health Assessment Questionnaires (SHAQ) according to the OMERACT criteria. HAQ Disability Index (HAQ-DI) values, Visual Analogue Scales (VAS) scores, and a novel aggregate SHAQ score averaging HAQ-DI values and the 5 disease-specific VAS scores were compared for their discriminate validity and sensitivity to change in patients with at least two completed SHAQs within a minimum period of 9 months. Possible risk factors for SHAQ score ≥1 were studied. Results: Truth, reliability, not analyzed before, and discriminate validity of the SHAQ and its scores fulfil the OMERACT criteria with differences among the different scores. SHAQ scores reflect the degree of organ involvement better than HAQ-DI and revealed a high sensitivity to change; organ-specific VAS scores were superior to identify changes in lung function parameters but failed to recognise cardiac or renal manifestations that were found to be reflected by SHAQ scores. Hand dysfunction, pain, the number of involved organs, and disease-specific manifestations such as of the gastrointestinal tract or digital ulcers provided risks for disability which impact depended on SSc subtype. Conclusions: The German SHAQ is a valid and reliable tool assessing functional disability in patients with SSc. The novel SHAQ score reflects disability and shows higher discriminate validity compared to HAQ-DI. SHAQ scores and organ-specific VAS scores can be recommended for clinical studies as validated and sensitive outcomes. Disclosure of Interest: None Declared